Cleft Lip and Palate Correction: The Utah Protocol - Andrea Battistini, MD; Jessica Lee Marquez, BA; Jack Scaife, BA; Lucia Collar, MD; Erinn Kim, MD; Dana Johns, MD; Duane Yamashiro, DDS; Barbu Gociman, MD, PhD (Plastic and Reconstructive Surgery, Global Open)
Background:. Cleft repair remains a contentious issue in craniofacial surgery, especially regarding the optimal timing and techniques. This study aims to present our institutions’ current protocol for cleft lip and palate repair, including alveolar bone grafting (ABG). Methods:. A total of 17 patients (20 clefts) treated with the latest protocol from 2016 to 2023 were evaluated. Demographic and clinical data were obtained from electronic charts. The protocol includes lip repair at 3 months, soft palate repair at 1 year, and hard palate closure with concurrent ABG at 2 years. Results:. Mean graft height and thickness scores were 2.3 and 2.2, respectively. Three clefts showed scores marginally below the threshold for thickness, potentially requiring regrafting. Malocclusion was minimal with no significant crossbites or velopharyngeal insufficiency. Conclusions:. Our modified protocol, emphasizing early hard palate closure with ABG, yields satisfactory outcomes in terms of graft height and thickness. Although long-term follow-up is warranted, our approach seems safe and efficient, potentially improving outcomes compared with traditional methods.